Algoritmo para la atención de enfermería de pacientes con complicaciones quirúrgicas en el posoperatorio inmediato con bypass gástrico: una revisión bibliográfica - Guamushig Jaque, Katheryn Mishel (2024)
Obesity is a risk factor that triggers different diseases, being unhealthy obesity the main cause of death. The first treatment to follow is through a healthy diet and physical activity. On the other hand, since it was not effective enough, surgical procedures were used, highlighting the gastric bypass as an effective treatment for obesity, giving favorable results to the metabolism, that is to say, it helps the sufficient release of insulin, decreasing diabetes complications. Objectives: Elaboration of an algorithm based on the bibliographic review, with the purpose of guiding the nursing staff to an adequate management of patients submitted to gastric bypass (GB) who have presented post - surgical complications. Methodology: A systemic analytical review of scientific articles was developed, with a descriptive qualitative approach. In addition to this, the relevant information obtained has been through reliable databases such as: PubMed and SciELO, by means of key words, being the form of selection of the information through inclusion and exclusion criteria, where 18 sources were selected for the support of the research developed. Results: The direct care of the patient after gastric bypass surgery should be specific, since it should cover the needs of the patient. Subsequently, provide specific education on the care to be taken by the patient after the surgical procedure. Likewise, to achieve comfort of the patient, together with their effective recovery, thus reducing their days of hospitalization.